Christ‐Centred Solidarity in a Time of Pandemic: The Theological Challenge to Contemporary Performances of Human Solidarity. Issue 4 (16th December 2020) - Muers, Rachel
Abstract: The article proposes a reading of Colossians 1:15‐20 for the time of COVID‐19, arguing that the assertion that all things "hold together" in the incarnate Christ should lead Christians not only to practise solidarity with those most at risk, but also to evaluate societal and systemic responses to COVID‐19 in the light of their effects on the most vulnerable members of society. The article considers the use and misuse of the rhetoric of self‐sacrificial love or loving self‐sacrifice, and the use and misuse of the image of warfare – arguing that in both of these areas, Christian communities offer urgent challenges and correctives on the basis of their traditions of Christ‐centred solidarity.